2016
DOI: 10.1016/j.conbuildmat.2015.12.075
|View full text |Cite
|
Sign up to set email alerts
|

A review on dynamic mechanical properties of natural fibre reinforced polymer composites

Abstract: Dynamic mechanical analysis (DMA) is a versatile technique that complements the information provided by the more traditional thermal analysis techniques such as differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and thermal mechanical analysis (TMA). The dynamic parameters such as storage modulus (E′), loss modulus (E″), and damping factor (Tan δ) are temperature dependent and provide information about interfacial bonding between the reinforced fibre and polymer matrix of composite mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
454
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 775 publications
(479 citation statements)
references
References 91 publications
15
454
0
10
Order By: Relevance
“…It is evident that the components of composites tend to decrease the molecular mobility (Ariawan et al 2015). Additionally, the gradual decrease in the Eʹ as the temperature increased indicated the highly crosslinked density of the composites, which meant a tighter network structure and higher stiffness (Saba et al 2016a;Duc et al 2014). This was due to the fact that the chain motions were perturbed in the immediate vicinity of the cross-links (Sreekala et al 2005).…”
Section: Storage Modulus (Eʹ)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident that the components of composites tend to decrease the molecular mobility (Ariawan et al 2015). Additionally, the gradual decrease in the Eʹ as the temperature increased indicated the highly crosslinked density of the composites, which meant a tighter network structure and higher stiffness (Saba et al 2016a;Duc et al 2014). This was due to the fact that the chain motions were perturbed in the immediate vicinity of the cross-links (Sreekala et al 2005).…”
Section: Storage Modulus (Eʹ)mentioning
confidence: 99%
“…Typically, the storage modulus (Eʹ) corresponds to the Young's modulus or the stiffness of the materials (Saba et al 2016a). The effect of SPF loading in the phenolic composites on the storage modulus is illustrated in Fig.…”
Section: Storage Modulus (Eʹ)mentioning
confidence: 99%
See 1 more Smart Citation
“…They are renewable, biodegradable, non-toxic, non-abrasive, they have low density with specific strength and low cost. Moreover, they are available worldwide been characterized as "environmentally-friendly" materials [16][17][18] . Sugarcane bagasse is the by-product obtained after sucrose extraction from the sugar cane plant or ethanol fuel plant.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers are defined as substances produced by plants or animals that can be used as composite reinforced [5,7]. The most common natural fibers are rami, kenaf, abaca, and others [8][9][10]. Based on previous studies researchers reported that natural fibers had big potential as composite reinforced [11].…”
Section: Introductionmentioning
confidence: 99%